An update on the use of cryoablation and immunotherapy for breast cancer - Olagunju, Akindele; Forsman, Tia; Ward, Robert C. (Frontiers in Immunology, 2022)
The use of cryoablation, a minimally-invasive image-guided technique to target and kill cancer cells, continues to gain traction within the medical field and with patients. This includes the use of cryoablation for the treatment of small breast cancers and focal sites of metastatic disease. In comparison to open surgical approaches, length of hospital stay and recovery time are decreased with the use of cryoablation. Research studies have also found that cryoablation may actually enhance tumor susceptibility to immunotherapy agents. Immunotherapy enhances a person’s own immune system to identify and attack cancer cells. It is proposed that after cryoablation there is increased expression of tumor specific antigens which the body can recognize as foreign invaders and with the combination of immunotherapy, result in an even more robust and efficient attack on the cancer cells. In this review we aim to highlight some of the recent advances in cryoablation which support the potential for cryoablation to induce these tumor-specific immune responses and thus supporting the use of combining cryoablation and immunotherapy for the treatment of breast cancer.